The implementation of restorative justice by magistrates, prosecutors and probation officers in sentencing of young offenders at selected district magistrate courts in the Western Cape - Gantana, Katrina (2006)
The qualitative study was conducted, within the judicial and social welfare system. Using convenience sampling (non-probability), magistrates, prosecutors and probation officers were specifically targeted to ascertain to what extend participants were currently implementing the approach of restorative justice in the sentencing of young offenders. Data was collected from charge sheets with regard to sentence remarks and the type of crime committed, and served as proof of implementation of such an approach. The study also explores the knowledge of these three professional groups with regard to restorative justice and their attitudes towards its implementation